Citation et textologie du journal : ce que vient faire l’infinitif de narration dans les colonnes des quotidiens - Frédéric Torterat (Discours)
This contribution deals with a specific use of the infinitive in the context of the French-speaking print media, and more particularly common representations of this type of expression in the daily newspapers. We are thus dealing here with the “narrative infinitive” as a grammatical construction, but also as a specific formula of media speech. According to our corpus, this use indicates how journalistic drafting stages the fact, in other words places it in a reconstruction, with intensification of the event, underlying a clearly polemical tone.The first part of this article presents the infinitive of narration in its linguistic sense, but also through the invariants which characterize it. The second part presents the implications of this type of verbal expression within the framework of daily newspaper textuality. In the last part, we show that the narrative infinitive can be seen as a singular predicative element, a significant variable of the journalistic drafting, which coincides moreover with “specific discursive elements”.